Emotional Agency at Work: The Development and Validation of a Measure - Hökkä, Päivi Kristiina; Räikkönen, Eija; Ikävalko, Heini; Paloniemi, Susanna; Vähäsantanen, Katja (Frontiers in Education, 2022)
Despite intensive research on agency in work environments, the topic remains underexplored through the lens of emotions. We here report the development and validation of a quantitative measure to explore emotional agency in working life. Empirical data were collected via a web-based survey within the professional domains of healthcare and real estate services. The questionnaire items were based on a theoretical construct of emotional agency at work. Exploratory factor analysis indicated that emotional agency includes two dimensions: Emotional Competence at Work and Influencing Emotions at Work. Exploratory structural equation modeling showed these dimensions to be equivalent across the studied professional domains. Furthermore, the convergent and discriminant validity of the measure was confirmed in relation to the emotional climate at work and work engagement. The study enriches current theory on agency and emotions at work by exploring their connection. It also proposes a novel measure of emotional agency at work (the E-Ag measure), offered as a useful tool for researching and developing working life and organizational behavior.